Economic Valuation of Coral Reefs Ecosystem in Bontosua Island, Pangkep Regency. - Irwansyah, Irwansyah; Massiseng, Andi Nur Apung; Ghurdi, Andi Bare (AgriSains, 2020)
This study aims to identify the potential and analyze the patterns of utilization of coral reefs in Bontosua Island, Pangkep Regency. The method used is the method of observation and in-depth interviews with a questionnaire that identifies the condition and use of coral reefs and calculates the value of use as a fish producer and as a tourist spot during. The results obtained indicate that the fact that the coral reefs on the island of Bontosua reach 80% with the economic value of direct coral reef benefits of Rp. 200,400,000 and an indirect economic value of Rp. 4,735,000,000. The conclusion of this research is that the economic value of the direct benefits of coral reefs on Bontosua Island is still very small, namely 4% while the value of indirect benefits reaches 95.9%.